2002
DOI: 10.1029/2001jb000401
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional inversion of marine magnetic anomalies on the equatorial Atlantic Ridge (St. Paul Fracture Zone): Delayed magnetization in a magmatically starved spreading center?

Abstract: [1] The St. Paul Fracture Zone (FZ) in the equatorial Atlantic is interrupted by three intratransform ridge (ITR) spreading centers. A detailed magnetic survey, corrected for the diurnal variations using a moored magnetic station, six submersible dives, and three bottom-towed video camera tracks provide data on the most eastern ITR (0°37 0 N, 25°27 0 W). Visual observations and submersible sampling displayed a high ultramafic/ volcanic ratio, supporting the assumption that the ITR is in a magmatically starved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…For example, beneath the smaller tectonized area between segment #11 and #10 where seawater has to cross ∼2 km thicker crust before reaching the upper mantle, the serpentinization process may be less intense producing no moderate magnetization anomaly but weak magnetization values relative to the segment centers. Serpentinization of peridotites has already been put forward by Sichler and Hékinian [2002] on a comparable amagmatic ridge section of the MAR. These authors explain a wider central magnetic anomaly than that expected by the Nuvel‐1 kinematic model by such a weathering process in a magmatically starved ridge section of the equatorial MAR which is thought to be related to a thermal minima in the upper mantle [ Bonatti , 1996].…”
Section: Discussionmentioning
confidence: 99%
“…For example, beneath the smaller tectonized area between segment #11 and #10 where seawater has to cross ∼2 km thicker crust before reaching the upper mantle, the serpentinization process may be less intense producing no moderate magnetization anomaly but weak magnetization values relative to the segment centers. Serpentinization of peridotites has already been put forward by Sichler and Hékinian [2002] on a comparable amagmatic ridge section of the MAR. These authors explain a wider central magnetic anomaly than that expected by the Nuvel‐1 kinematic model by such a weathering process in a magmatically starved ridge section of the equatorial MAR which is thought to be related to a thermal minima in the upper mantle [ Bonatti , 1996].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the magnetization from serpentinized peridotite is also a candidate for marine magnetic anomalies. Some observational studies have suggested that induced magnetization in serpentinized peridotite can also contribute to observed magnetic anomalies [e.g., Tivey and Tucholke , 1998; Sichler and Hékinian , 2002; Hosford et al , 2003; Okino et al , 2004]. Experimental and field studies of rock magnetism also show that magnetite is crystallized through extensively serpentinized peridotite with high natural remanent magnetization (NRM) (4–10 A/m) and magnetic susceptibility (∼0.07, average), giving an indication of induced magnetization [ Oufi et al , 2002].…”
Section: Discussionmentioning
confidence: 99%
“…The magnetization solution of survey box B shows a shift toward more positive magnetization values toward the distal part of the flanks. As such a long wavelength signal in the result of the inversion is always suspect, we have also calculated the crustal equivalent magnetization using a generalized inversion method [e.g., Sichler and Hékinian , 2002] which generates no spurious long wavelength component. This method is based on a linear discrete inversion taking as unknowns the magnetization of parallelepiped shaped prisms which fit the topography.…”
Section: Data Collection and Processingmentioning
confidence: 99%